Holocene overflow events of the lower Yellow River recorded in Huangdun ancient lake, northern Jiangsu Plain, China - Rui Zhang; Li Xing; Shi‐Yong Yu; Junsheng Nie; Jinjia Wu; Zhao Wang; Shiyue Chen; Zhanfang Hou; Guodong Zhang; Denghui Zhang (Journal of Quaternary Science, 2024)
Overflow events are important embodiments of the evolutionary characteristics of the lower Yellow River. Lakes in the lower reaches of the Yellow River have the capacity to record these events. Due to the complex provenance and transport pathways of sediments in local lakes, it is difficult to extract reliable information on sediments delivered by the Yellow River based on conventional methods and proxies. Here, we show results from a genetically meaningful end‐member (EM) decomposition of sediment grain‐size data from Huangdun ancient lake. The grain‐size of the sediments can be decomposed into three end‐members. Comprehensive analysis combining environmental magnetism and geochemical indicators clarifies the significance of each end‐member. EM1 represents mixed signals of various proximal fluvial sediments and the Yellow River materials. EM2 is similar to terrestrial fine‐grained debris in conjunction with local pedogenic materials, aeolian inputs and some Yi River materials. EM3 represents a component that is mainly derived from long‐distance transport by the lower Yellow River. End‐member analysis successfully identified overflow events of the lower Yellow River on a southward‐flowing path during the Holocene. This study provides a meaningful attempt to reconstruct the evolutionary history of the lower Yellow River from sedimentary records.

Luminescence chronology of the Palaeolithic–Neolithic transition in the Yujiagou site at the Nihewan Basin, northern China - Xue Rui; Yu‐Jie Guo; Jia‐Fu Zhang; Yue Hu; Hui‐Jie Mei; You‐Ping Wang; Fei Xie; Bo Li (Journal of Quaternary Science, 2019)
The relationship between the Palaeolithic–Neolithic cultural transition and environmental changes is important for understanding human history. However, the timing and nature of human behaviour at the transition, and their relationship to local environmental conditions, remain poorly understood. The Yujiagou archaeological site in the Nihewan Basin, northern China, provides valuable chronological and archaeological information about cultural changes in northern China due to its continuous archaeological sequence of cultural layers from the Palaeolithic to Neolithic. In this study, we apply post‐infrared infrared stimulated luminescence (pIRIR) dating on individual feldspar grains to date the Yujiagou deposits. We provide a revised chronology for the archaeological sequence at the site. We combine these results with multi‐proxy climatic indicators to gain insights into palaeoenvironmental changes in the region. The results show that the age of the artefact‐bearing deposits ranges from 13.5 to 9.7 ka. Polished stones and pottery begin to occur in the archaeological layer around 13 ka, corresponding to a transitional period when the local climate changed from cold to warm. This site provides evidence for understanding the process that led to the regional transition from hunter‐gathering to farming.